Eating‐related Environmental Factors in Underweight Eating Disorders and Obesity: Are There Common Vulnerabilities During Childhood and Early Adolescence?. (21st November 2012) - Krug, I.; Villarejo, C.; Jiménez‐Murcia, S.; Perpiñá, C.; Vilarrasa, N.; Granero, R.; Cebolla, A.; Botella, C.; Montserrat‐Gil de Bernabe, M.; Penelo, E.; Casella, S.; Islam, M. A.; et al.
Abstract Objective This study aimed to examine whether there is an association between individual, social and family influences and dysfunctional eating patterns early in life and the likelihood of developing a subsequent underweight eating disorder (ED) or obesity. Method The total sample comprised 152 individuals (underweight ED, n = 45; obese patients, n = 65; healthy controls; n = 42) from Barcelona, Spain. The Cross‐Cultural Questionnaire (CCQ) was used to assess early eating influences as well as individual and family eating patterns and attitudes towards food. Results Even though a few shared eating influences emerged for both groups, unique factors were also observed. Whereas relationship with friends, teasing about eating habits by family members and the mass media were of specific relevance to the underweight ED group, the patient's own physical appearance, body dissatisfaction, teasing about eating habits by friends, teasing about body shape by family members and dysfunctional eating patterns were unique to obesity. Conclusions Overlapping environmental risk factors provide evidence for integral prevention and intervention approaches that simultaneously tackle a range of weight‐related problems. The unique factors might be important for targeting high‐risk individuals. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.